Biodiesel degradation mechanism upon exposure of metal surfaces: A study on biodiesel sustainability. (15th February 2022) - Fazal, M.A.; Rubaiee, Saeed; Al-Zahrani, A.; Ghazali, Sami
Graphical abstract: Highlights: Palm biodiesel consists of 57.24% saturated and 42% unsaturated esters. The degradation mechanism of unsaturated ester differs from that of saturated ester. The oxidation of unsaturated molecules occurs at its allylic or bis-allylic sites. Palmitate, oleate, linoleate are significantly reduced in Cu exposed biodiesel. Change in biodiesel composition hinders its sustainability. Abstract: The increased demand and price of petroleum diesel along with its limited reservation and emitted harmful substances have made the world confronted. Biodiesel as an alternative to petroleum diesel offers immediate potential to meet these concerns. It provides several technical benefits over diesel such as reduced emission, high flash point, and improved cetane number. However, the oxidative nature of biodiesel is found to be one of the major problems which limits its commercial usage and sustainability. Molecular reactions in biodiesel and their susceptibility to oxidation are important to understand but only limited information is available in this regard. The present study aims to investigate the biodiesel molecular changes upon exposure of metal surface. The tests were conducted by immersing copper coupons in palm biodiesel at ambient temperature (25–27 ˚C) for various immersion time, viz., 200 h, 600 h, 1200 h, 2880 h. Density, total acid number and composition of biodiesel before and after immersion tests were determined by density meter, TAN analyzer and gas chromatography mass spectroscopy analysis. Date obtained from different tests are analyzed and compared to explore the possible degradation mechanism of biodiesel molecules. Results show that the key components of biodiesel include methyl stearate (9.94%), palmitate (38.64%), oleate (34.29%) and linoleate (6.92%). Upon exposure of copper for 2880 h, the concentrations of these molecules are changed to 10.14%, 33.78%, 31.34% and 1.09% respectively. Such changes in composition cause alteration in fuel properties and thus, hinders its sustainability. The possible reaction mechanisms have been discussed in detail with the help of obtained data and relevant literatures.